2017
DOI: 10.1021/acs.jnatprod.6b01151
|View full text |Cite
|
Sign up to set email alerts
|

Corymbulosins D–H, 2-Hydroxy- and 2-Oxo-clerodane Diterpenes from the Bark of Laetia corymbulosa

Abstract: A bioactive CH3OH–CH2Cl2 (1:1) extract of the bark of Laetia corymbulosa provided five new clerodane diterpenes with an isozuelanin skeleton, designated as corymbulosins D–H (1–5), as well as the known corymbulosins B (6) and C (7), for which the relative configurations were not previously determined. The structures of 1–5 were characterized on the basis of 1D and 2D NMR spectroscopic and HRMS analysis. The absolute configurations of all isolated compounds 1–7 were verified through chemical methods, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Taking into consideration the six units of unsaturation that were confirmed in 1 (two acetoxy groups, a propionate group, and three double bonds), as well as 13 C NMR-derived evidence for the presence of a keto carbonyl (δ C 207.9, C-6), it was concluded that the remaining three units of unsaturation could be accounted for as three rings. Bearing this in mind, an analysis of the 1 H– 1 H COSY and HMBC correlation data (Figure ) led to the proposal that 1 featured a tricyclic clerodane diterpene core. More specifically, compound 1 belongs to a subgroup of clerodane diterpenes that possess an isozuelanin skeleton . However, in contrast to the reported isozuelanin-containing natural products that bear a methylene, a hydroxy, or an alkoxy group at C-6, metabolite 1 is the first member of this class to feature a C-6 keto carbonyl group …”
Section: Resultssupporting
confidence: 87%
“…Taking into consideration the six units of unsaturation that were confirmed in 1 (two acetoxy groups, a propionate group, and three double bonds), as well as 13 C NMR-derived evidence for the presence of a keto carbonyl (δ C 207.9, C-6), it was concluded that the remaining three units of unsaturation could be accounted for as three rings. Bearing this in mind, an analysis of the 1 H– 1 H COSY and HMBC correlation data (Figure ) led to the proposal that 1 featured a tricyclic clerodane diterpene core. More specifically, compound 1 belongs to a subgroup of clerodane diterpenes that possess an isozuelanin skeleton . However, in contrast to the reported isozuelanin-containing natural products that bear a methylene, a hydroxy, or an alkoxy group at C-6, metabolite 1 is the first member of this class to feature a C-6 keto carbonyl group …”
Section: Resultssupporting
confidence: 87%
“…C. laevigata , which is called the glossy laurel or red-fruited laurel, are distributed in rainforest areas, mainly in eastern Australia. Only two phytochemical researches of this species have been reported so far. , In our continuous investigation of rainforest plants, ,, we performed a phytochemical study on a 50% MeOH/CH 2 Cl 2 extract (N025439) of the leaves and twigs of C. laevigata . In this study, six new δ-lactone derivatives, named cryptolaevilactones A–F ( 1 – 6 ; Figure ), were isolated from the EtOAc-soluble portion of the extract.…”
mentioning
confidence: 99%
“…All isolates were evaluated for antiproliferative activity against five human cancer cell lines, A-549, MDA-MB-231, KB, KB-VIN, and MCF-7, using the sulforhodamine B (SRB) method with vincristine (VIN) and paclitaxel (PXL) as positive controls . All of the compounds, except 2 and 14 , exhibited antiproliferative activity (IC 50 2.6–8.3 μM) against multidrug-resistant KB subline KB-VIN (Table ).…”
Section: Resultsmentioning
confidence: 99%